2018
DOI: 10.1111/jfr3.12498
|View full text |Cite
|
Sign up to set email alerts
|

Flood modelling using synthesised citizen science urban streamflow observations

Abstract: The increase in floods and flash floods over the last decades has motivated researchers to develop improved methodologies for flood risk prevention and warning. Flood forecasting models available today have evolved technologically but are subject to limitations due to the lack of data and limited community participation. This paper presents the Hydrological Alert Model with Participatory Basis (HAMPB) model, an approach for integrating water level data reported by citizens, which has the advantage of being ine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The Mineirinho catchment has a history of recurrent flooding, particularly over the past decade, leading to significant economic loss due to growing commercial establishments in the city (Fava et al, 2018;de Abreu et al, 2019). There have been attempts to manage this regular flooding by rectifying and/or channelizing the rivers and streams within the city leading to exacerbation of flooding in the city's lowlands.…”
Section: Study Areamentioning
confidence: 99%
“…The Mineirinho catchment has a history of recurrent flooding, particularly over the past decade, leading to significant economic loss due to growing commercial establishments in the city (Fava et al, 2018;de Abreu et al, 2019). There have been attempts to manage this regular flooding by rectifying and/or channelizing the rivers and streams within the city leading to exacerbation of flooding in the city's lowlands.…”
Section: Study Areamentioning
confidence: 99%
“…The third data type I mentioned above is where I see the most potential to advance in the “big data” age. In my opinion, we now have a unique opportunity to exceptionally advance flood modelling capability and accuracy thanks to the advances in remote sensing‐based data products and technologies (Coops, Kearney, Bolton, & Radeloff, ; Shen, Anagnostou, Allen, Brakenridge, & Kettner, ), big data science (Jianga, Zheng, Babovic, Tian, & Han, ; Manfreda & Samela, ; Mobley, Sebastian, Highfield, & Brody, ; Pollard, Spencer, & Jude, ), and integration of citizen observations into modelling (Assumpção, Popescu, Jonoski, & Solomatine, ; Fava, Abe, Restrepo‐Estrada, Kimura, & Mendiondo, ; Rollason, Bracken, Hardy, & Large, ; Wang, Mao, Wang, Rae, & Shaw, ). In recent years, remote‐sensing techniques have shown encouraging results in delineating water surfaces and estimating water levels (Ciana, Marconcini, & Ceccato, ; Clement, Kilsby, & Moore, ; Huang et al, ; Pekel, Cottam, Gorelick, & Belward, ).…”
mentioning
confidence: 99%
“…Although some authors assigned possible values of flood memory parameters adopted in Equation ( 3), future flood risk assessment works should consider alternatives for validate its parameters. Citizen science opportunities have demonstrated that observations, knowledge, and beliefs from locals can provide valuable measures in ungauged basins and outline possible changes in behaviour (Abreu, 2019;Fava et al, 2019;Mondino et al, 2020;Souza et al, submitted). Therefore, citizens' engagement is not only a data source, but it can be a step toward risk reduction and resilience increase as well (Mao et al, 2017).…”
Section: Resultsmentioning
confidence: 99%